The role of yellow lupin (Lupinus luteus) in the decline affecting oak agroforestry ecosystems - SERRANO, M S; FERNÁNDEZ-REBOLLO, P; DE VITA, P; CARBONERO, M D; SÁNCHEZ, M E (Forest Pathology, 2011)
Phytophthora cinnamomi is a soilborne pathogen causing root rot in Mediterranean Quercus species growing in dehesa rangeland ecosystems. Recently, it has been reported causing wilting and death of Lupinus luteus (yellow lupin), a spontaneous plant in southern Spain rangelands, but also frequently sowed for livestock grazing. In soils artiﬁcially infested with P. cinnamomi chlamydospores and planted with diﬀerent cultivars of yellow lupin, a signiﬁcant increase in the density of propagules was detected in comparison with the initial levels of inoculum and with the infested but not planted soil (control). In oak-rangelands in which yellow lupine was planted, isolation and counting of colonies of P. cinnamomi from soil samples have shown the ability of this plant to maintain or even increase the inoculum density and thus facilitate the infection of trees. Results suggested that cultivation of yellow lupin in oak-rangeland ecosystems should be avoided whether oak trees are aﬀected by root disease caused by P. cinnamomi or not. This leguminous plant can act as an inoculum reservoir or even enhance inoculum soil levels available for oak root infections, exacerbating the oak decline severity in the region.
Keywords: inoculum density (voyant); Lupinus luteus; Oak decline; phytophthora cinnamomi; root disease

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C M; SCOTT, J K (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease

European oak declines and global warming: a theoretical assessment with special reference to the activity of Phytophthora cinnamomi - Brasier, C. M.; SCOTT, J. K. (EPPO Bulletin, 1994)
Causes of current severe declines of the deciduous oaks Quercus robur and Q. petraea in northern and central Europe and of the evergreen Q. ilex, Q. suber and other Quercus spp. in the Mediterranean area are reviewed. Factors implicated include drought, pollution, winter cold, flooding, and stress-related attacks by insects and fungi. Additional factors in Mediterranean oak declines include changing land-use patterns and root disease caused by the aggressive, exotic oomycete root pathogen Phytophthora cinnamomi. Under conditions of global warming the survival and degree of root disease caused by this fungus seems likely to be enhanced, while the host range of the organism might also be increased. Application of the CLIMEX climate-matching program suggests that with a mean increase in temperatures of 1.5–3°C the fungus might considerably increase its disease activity in its existing locations, and to some extent spread northwards and eastwards. However, it seems unlikely to become significantly active in areas of Europe with colder winters such as parts of Scandinavia, Russia and the central Danube. The predictive value of research on major environmental problems such as oak declines could be enhanced by more highly coordinated European forestry research programmes.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Oak decline; phytophthora cinnamomi; range expansion (PG); root disease